2020
DOI: 10.3389/fped.2020.573099
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA TUG1 Modulates Expression of Elastin to Relieve Bronchopulmonary Dysplasia via Sponging miR-29a-3p

Abstract: Objective: Multiple studies have highlighted that long non-coding RNAs (lncRNAs) may exert paramount roles in relieving bronchopulmonary dysplasia (BPD). The aim of our investigation is to probe the role and mechanism of lncRNA taurine upregulated gene 1 (TUG1) in BPD. Methods:The current mouse model of BPD was simulated by induction of hyperoxia, and hyperoxia-induced mouse type II alveolar epithelial (MLE-12) (MLE-12) cells were established as a cellular model. Quantitative real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…With the mounting discovery of several non‐coding RNAs, including miRNAs, lncRNAs, and circRNAs, more spotlights have been focused on exploring their relationship with BPD. Recent data show that circRNAs and the downstream target genes play crucial roles in various biological processes associated with damage repair after immaturity lung injury 7,33,34 . Therefore, it is essential to investigate the interactions and regulatory mechanisms of the ceRNA network in the development and progression of BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the mounting discovery of several non‐coding RNAs, including miRNAs, lncRNAs, and circRNAs, more spotlights have been focused on exploring their relationship with BPD. Recent data show that circRNAs and the downstream target genes play crucial roles in various biological processes associated with damage repair after immaturity lung injury 7,33,34 . Therefore, it is essential to investigate the interactions and regulatory mechanisms of the ceRNA network in the development and progression of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that circRNAs and the downstream target genes play crucial roles in various biological processes associated with damage repair after immaturity lung injury. 7,33,34 To elucidate the molecular processes and pathways that underlie complex diseases, ceRNA regulation network analysis is a powerful approach. A recent study revealed that in the LPS-induced lung injury model, circRNA was functional as miRNA sponges that interacted with hsa-miR-4688 and hsa-miR-3192-5p in the inflammation process of Human bronchial epithelial (BEAS-2B) cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…miR29a-3p, miR449a-5p, and miR147-3p have been reported to be accumulated in exosomes derived from oral squamous cells, macrophages, and bronchoalveolar lavage uid [53,55,96,97]. In addition, upregulation of miR29a-3p rescues bronchopulmonary dysplasia and has a negative regulatory effect on the Smad, NFκB, and canonical Wnt signaling pathways [98][99][100]. Importantly, miR29a-3p directly targets the Wnt-related genes DVL3 (Dishevelled 3), CSNK2A2 (casein kinase 2 alpha 2 polypeptide), FZD3 (Frizzled family receptor 3), and FZD5 (Frizzled family receptor 5) [100].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse alveolar epithelial cells MLE‐12 were purchased from American Type Culture Collection (ATCC) and cultured in RPMI‐1640 medium with 10% foetal calf serum (FCS) and penicillin/streptomycin (100 U ml −1 ). They were then incubated in a 5% CO 2 incubator at 37°C (Zhong et al, 2020). Next, the cells were inoculated in a six‐well plate and cultured for 24 h. After exposure to the medium supplemented with 0.1% FCS for 6 h, the cells were kept in indoor air (21% O 2 ) or hyper oxygen (85% O 2 ) for 6 h (Chen et al, 2017; Chen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%